Mechanism of governance, societal institutions, and state bureaucracy: concerns on societal institutions and governmental porosity - Ribeiro, José Mendes (2022)
This essay discusses mechanisms of participative governance in public sector supported on theories of civil liberties, dialogical democracies, patterns of state bureaucracies, and public governance reforms. Object is analysis of effects of these issues on political agendas and alternatives of public and participative governance in Brazil with emphasis on conflicts among govern, politicians, civil servants, interest groups, and advocacy coalitions struggling in policy making. The article signals for a hybrid character of Brazilian democracy where Weberian universalism and rules of Welfare State institutions inscribed in 1988 constitutional operates through competition between two logics – stratum inheritance of state bureaucracy in one side, and initiatives in favor of horizontal and participative governances to the other side. Dynamic contradictions among these for issues will define the pattern of present competition for State apparatus.